Impact of health education on preventive measures of Rabies among primary school teachers in Mandalay, Myanmar - Aung, Ei Ei Phyo; Htun, Nang Mie Mie; Soe, Pa Pa (International Journal Of Community Medicine And Public Health, 2021)
Background: Rabies is an exceptionally fatal zoonotic disease and major public health problem in developing countries. Health knowledge of preventive measures of rabies among primary school teachers is paramount to cultivate their students and create a secure and safe environment since primary school students are the most vulnerable group. The study aimed to assess the effect of health education on knowledge of preventive measures of rabies among primary school teachers. Methods: A pre and post-test intervention study was conducted among randomly selected 64 primary school teachers from 7 Townships in Mandalay from July to October, 2020. An educational intervention was conducted by contributing 4 sheets of pamphlets and appearing 5 minutes education video record and reassessment was done one month later. Results: The mean knowledge scores before and after intervention were 40.59±4.85 and 47.75±4.02 showing statistically significant improvement (p<0.001). Mean of the improvement percentage was 19.38±5.06. Out of 64 participants, 37.5% had good knowledge in pre-test which improved to 95.3% in post-test (p<0.05). Although, age, marital status, having children and having stray dogs near school compound were adjusted in multiple linear regression, there was no statistical significance association with improvement percentage. Conclusions: There is improvement of knowledge status, which is not influenced by sociodemographic factors, following educational intervention. This highlights the need of continuing medical education for preventive measures of rabies for both primary school teachers and primary school students.